Pemanfaatan Media Sosial Instagram untuk Meningkatkan Kesadaran Penggunaan Kata Baku Bahasa Indonesia - Elfara Zahra Pranomo; Fany Haifa Alia; Respi Nurdian; Adinda Dewi Lestari; Anisa Apriliani; Yuni Ertinawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The research aims to examine awareness of the use of standard indonesian words through soscial media namely. With the davelopment of social medai, the language used tends to be freer and less struvtured. The research method used is a qualitative method with a case study approach on accounts that focus on indonesian language learning. Data isi collected through observation of uploaded content as well as analysis of audience and follower interaction. The reserach results show tha the use of instagram can be an effective medium in introducing and educating the oublic about the importance of using standard words. The interactions that occur between account managers and followeres help strengthen understanding and practice of using indonesian properly and correctly. It can be concluded that 75% of instagram accounts still need coaching regarding standard words and 35% have had increased coaching so that this research is expected to be a focus for instagram users tp be wiser in using social media.